Pasar Resisting Mall: a Cross-Cultural Ethnographic of Economic Traditional Market - Hasanah, Noviy (Shirkah: Journal of Economics and Business, 2018)
Yogyakarta since the late ten years has shifted an economic direction taking impacts on such economic sectors as that of pasar (Javanese traditional market). Pasar, as a daily space for economic interaction of the society to be threatened by the increasingly numbers of malls. This article critically tells the story of Gowok small trader resistance to the existence of a nearby mall. Doing ethnography for several months and in-depth interviews with some small traders, the author who comes from non-Javanese native have reflectively analyzed the cultural economy of the Javanese people. This article argues that market traders of pasar Gowok has transformed the pattern of buying and selling behavior and increased the variety of merchandise. Keywords: mall, Yogyakarta, pasar, traditional market, Javanese